Effectiveness of antimicrobial therapy for community-acquired pneumonia in real clinical practice - O. M. Uryasev; A. V. Shakhanov; L. V. Korshunova (Бюллетень сибирской медицины)
Background. Community-acquired pneumonia (CAP) remains one of the most common infectious diseases, occupying an important place in the structure of mortality worldwide.Aim. To evaluate the effectiveness of antimicrobial therapy for community-acquired pneumonia in hospitalized patients in real clinical practice.Materials and methods. A retrospective, observational study was conducted, which included 236 patients hospitalized for community-acquired pneumonia at the Regional Clinical Hospital in Ryazan in 2019. Based on these case histories, an analysis of the effectiveness of the initial empiric antimicrobial therapy was performed.Results. The initial empiric antimicrobial therapy in 73% of cases included administration of ceftriaxone, in 45% of cases – levofloxacin, in 14% of cases – azithromycin. It was found that initial antimicrobial therapy was effective in 58% of patients who did not require replacement for the antibiotic. A need for a change in the treatment regimen was significantly associated with an increase in the length of hospitalization (p < 0.001), heart rate upon admission (p = 0.032), myelocyte count in the complete blood count (p < 0.001), and urea and blood creatinine levels (p = 0.004 and p = 0.044, respectively). The selected antimicrobial therapy regimen was significantly associated with the expected treatment effectiveness (p = 0.039). The choice of levofloxacin in monotherapy or in combination with ceftriaxone was accompanied by a decrease in the relative risk of replacing the antimicrobial, compared with other treatment regimens (odds ratio (OR) = 0.86 (95% confidence interval (CI): 0.55–1.34) and OR = 0.57 (95% CI: 0.37–0.87), respectively).Conclusion. Empiric antimicrobial therapy for community-acquired pneumonia in real clinical practice complies with current recommendations, however, at the same time, its ineffectiveness persists. Respiratory fluoroquinolones are most effective in treating pneumonia in hospitalized patients.